Resuscitation of Dormant “Non-culturable” Mycobacterium tuberculosis Is Characterized by Immediate Transcriptional Burst - Salina, Elena G.; Grigorov, Artem S.; Bychenko, Oksana S.; Skvortsova, Yulia V.; Mamedov, Ilgar Z.; Azhikina, Tatyana L.; Kaprelyants, Arseny S. (Frontiers in Cellular and Infection Microbiology, 2019)
Under unfavorable conditions such as host immune responses and environmental stresses, human pathogen Mycobacterium tuberculosis may acquire the dormancy phenotype characterized by ‘non-culturability’ and a substantial decrease of metabolic activity and global transcription rates. Here, we found that the transition of M. tuberculosis from the dormant ‘non-culturable’ (NC) cells to fully replicating population in vitro occurred not earlier than 7 days after the start of the resuscitation process, with predominant resuscitation over this time interval evidenced by shortening apparent generation time up to 2.8 h at the beginning of resuscitation. The early resuscitation phase was characterized by constant, albeit low, incorporation of radioactive uracil, indicating de novo transcription immediately after the removal of the stress factor, which resulted in significant changes of the M. tuberculosis transcriptional profile already after the first 24 h of resuscitation. This early response included transcriptional upregulation of genes encoding enzymes of fatty acid synthase system type I (FASI) and type II (FASII) responsible for fatty acid/mycolic acid biosynthesis, and regulatory genes, including whiB6 encoding a redox-sensing transcription factor. The second resuscitation phase took place 4 days after the resuscitation onset, i.e., still before the start of active cell division, and included activation of central metabolism genes encoding NADH dehydrogenases, ATP-synthases, and ribosomal proteins. Our results demonstrate, for the first time, that the resuscitation of dormant NC M. tuberculosis is characterized by immediate activation of de novo transcription followed by the upregulation of genes controlling key metabolic pathways and then, cell multiplication.